2021
DOI: 10.3390/agronomy11040723
|View full text |Cite
|
Sign up to set email alerts
|

Use of Controlled-Release Urea to Improve Yield, Nitrogen Utilization, and Economic Return and Reduce Nitrogen Loss in Wheat-Maize Crop Rotations

Abstract: Excessive nitrogen (N) fertilizer input has become a common phenomenon among most farmers in the winter wheat–summer maize rotation system of north-central China, and has resulted in low nutrient use efficiency and environmental pollution. Controlled-release urea (CRU) is proposed as a solution to excessive fertilization because CRU achieves high yields and reduces N losses. Therefore, CRU mixed with normal urea at rates based on the Nutrient Expert (NE) system was used as fertilizer in a 4-year field experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Furthermore, the utilization of slow-or controlled-release nitrogen fertilizers has been shown to improve nitrogen use efficiency (NUE) and diminish nitrogen loss [53,69], mainly by mitigating nitrate leaching, volatilization, and nitrous oxide emissions, The gradual release of fertilizer from a polymer coating occurs upon the accumulation of a critical volume of the saturated solution. At this point, there are two ways in which the nutrients can be released [11].…”
Section: The Pros and Cons Of Srn And Crn Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the utilization of slow-or controlled-release nitrogen fertilizers has been shown to improve nitrogen use efficiency (NUE) and diminish nitrogen loss [53,69], mainly by mitigating nitrate leaching, volatilization, and nitrous oxide emissions, The gradual release of fertilizer from a polymer coating occurs upon the accumulation of a critical volume of the saturated solution. At this point, there are two ways in which the nutrients can be released [11].…”
Section: The Pros and Cons Of Srn And Crn Applicationmentioning
confidence: 99%
“…Furthermore, the utilization of slow-or controlled-release nitrogen fertilizers has been shown to improve nitrogen use efficiency (NUE) and diminish nitrogen loss [53,69], mainly by mitigating nitrate leaching, volatilization, and nitrous oxide emissions, resulting in a diminished environmental footprint when compared to conventional nitrogen fertilizers [1]. Additionally, slow-and controlled-release nitrogen fertilizers can increase crop yields by providing a steady supply of nitrogen to the plants.…”
Section: The Pros and Cons Of Srn And Crn Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher P concentrations and accumulation amount of leaves might contribute to the transport of carbohydrates from leaves to grain, which resulted in the higher yield in the different optimal managements than FPT treatment (Table S3 and Table 4; Figure 1). Compared to the blended fertilizer, the controlled release fertilizer can effectively control the release rate of nutrients, promote the absorption of nitrogen nutrients, and meet the needs of crops at the later stage of growth, so as to improve the yield and fertilize utilization efficiency [52,53]. Studies have shown that the new fertilizers can extend their availability in the soil and thus improve utilization efficiency [54].…”
Section: The Different Fertilization Strategies Affect Nutrient Accum...mentioning
confidence: 99%
“…The excessive use of nitrogen (N) fertilizers can have several negative effects on the environment [18]. A previous study showed that the use of controlled-release nitrogen fertilizers at sowing increased the crop yield, WUE, and economic returns by 8.5%, 10.9%, and 11.3%, respectively [19]. Another study on N fertilizers in the Loess Plateau reported that the application of an appropriate amount of N fertilizer increased the content of total wheat protein and composition of protein, leading to an improvement in the baking quality of wheat flour [20].…”
Section: Introductionmentioning
confidence: 99%